2010
DOI: 10.1111/j.1467-9531.2010.01231.x
|View full text |Cite
|
Sign up to set email alerts
|

6. The Simultaneous Decision(s) about the Number of Lower- and Higher-Level Classes in Multilevel Latent Class Analysis

Abstract: Recently, several types of extensions of the latent class (LC) model have been developed for the analysis of data sets having a multilevel structure. The most popular variant is the multilevelLC model with finite mixture distributions at multiple levels of a hierarchical structure; that is, with LCs for both lower-level units (e.g. individuals, citizens, or patients) and higher-level units (e.g. groups, regions, or hospitals

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
116
2
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 120 publications
(120 citation statements)
references
References 43 publications
0
116
2
2
Order By: Relevance
“…In this study, to obtain the optimal number of clusters, log-likelihood (LL), Akaike information criterion (AIC), AIC3 and the Bayesian information criterion (BIC) were used. The model was chosen based on the results of the study of Lukočienė, Varriale, and Vermunt (2010), which includes a simulation demonstrating why BIC is the right fit index. Thus, the BIC value was used as a criterion for model selection.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, to obtain the optimal number of clusters, log-likelihood (LL), Akaike information criterion (AIC), AIC3 and the Bayesian information criterion (BIC) were used. The model was chosen based on the results of the study of Lukočienė, Varriale, and Vermunt (2010), which includes a simulation demonstrating why BIC is the right fit index. Thus, the BIC value was used as a criterion for model selection.…”
Section: Resultsmentioning
confidence: 99%
“…In the literature, it is stated that there are disadvantages to including predictors in models when determining the number of latent classes and it is suggested that a three-step analysis is employed in order to compensate for these disadvantages (Gudicha and Vermunt, 2013;Vermunt, 2010). For this reason, this study is significant both for the way it departs from the work reported in the literature in terms of the process of including predictor variables in the model, and presenting the model used in the work.…”
Section: Introductionmentioning
confidence: 99%
“…Or, per the second approach discussed earlier, another latent classification variable can be added-here, a Level 2 classification variable-and Level 1 latent class membership can be made dependent on Level 2 latent class membership. This implies local independence of outcomes per person given a combination of Level 1 and Level 2 class membership (Lukociene, Varriale, & Vermunt, 2010). It is also possible to use these two approaches in one model.…”
Section: Additional Mixture Models Using the Two Approaches For Relaxmentioning
confidence: 99%
“…The fact that the BIC performance needs to be scrutinized is illustrated by the fact that, for the application, the BIC selected seven clusters, which appears to be an overselection when comparing cluster-specific factors and considering the (lack of) interpretability and stability of the clustering. Adaptations that will be considered include the hierarchical BIC (Zhao, Jin, & Shi, 2015;Zhao, Yu, & Shi, 2013) and stepwise procedures like the one described by Lukočienė, Varriale, and Vermunt (2010). Their performances will be investigated and compared, also for the more intricate case wherein the number of factors might vary across clusters.…”
Section: Discussionmentioning
confidence: 99%